Unraveling Neuroendocrine Gallbladder Cancer: Comprehensive Clinicopathologic and Molecular Characterization. (8th March 2021) - de Bitter, Tessa J. J.; Kroeze, Leonie I.; de Reuver, Philip R.; van Vliet, Shannon; Vink-Börger, Elisa; von Rhein, Daniel; Jansen, Erik A. M.; Nagtegaal, Iris D.; Ligtenberg, Marjolijn J. L.; van der Post, Rachel S.
Abstract : PURPOSE: Neuroendocrine carcinomas and mixed neuroendocrine non-neuroendocrine neoplasms of the gallbladder (NE GBC) are rare and highly aggressive entities. The cell of origin of NE GBC has been a matter of controversy. Here, we performed a comparative histopathologic and molecular analysis of NE GBC cases and, if present, associated precancerous lesions. PATIENTS AND METHODS: We selected cases diagnosed between 2000 and 2019 in the Netherlands. Precursors and carcinomas were immunohistochemically compared and analyzed for mutations, gene amplifications, microsatellite instability, and tumor mutational burden using an next-generation sequencing panel containing 523 cancer-related genes. In addition, presence of fusion genes was analyzed using a panel of 55 genes. RESULTS: Sixty percent of neuroendocrine cases (6/10) presented with a precursor lesion, either intracholecystic papillary neoplasm (n = 3) or biliary intraepithelial neoplasia (n = 3). Immunohistochemically, neuroendocrine components were different from the epithelial precursor lesions. Molecular profiling, however, revealed TP53 mutations shared between different components in five of six cases, indicating a clonal relation. Furthermore, 40% of cases (4/10) harbored at least one potentially actionable alteration. This included (likely) pathogenic mutations in RAD54L, ATM, and BRCA2 ; amplifications of ERBB2 and MDM2 ; and a gene fusion involving FGFR3-TACC3 . All cases were microsatellite-stable and had a tumor mutational burden of < 10 mutations/Mb. CONCLUSION: Our data provide insight into the development of NE GBC and suggest a common origin of precancerous epithelial lesions and invasive neuroendocrine components, favoring the hypothesis of lineage transformation. Moreover, nearly half of the NE GBCs carried at least one potentially actionable molecular alteration, highlighting the importance of molecular testing in this highly lethal cancer.